P34 What Is Integrated Care And What Is The Value Of An Integrated Respiratory Specialist?. (10th November 2014) - Roberts, NJ; Ward, M; Patel, IS; Yorke, J; Williams, J; Walters, R; McKevitt, M; Edwards, S
Abstract : Aim: The way we deliver healthcare in the UK is changing, joining up care between the different health sectors has created a new field of "integrated care". Recent publications from the Kings Fund, Nuffield Trust and National Voices has shown that it is difficult to define "integrated care". This project surveyed health professionals on their views about integrated care and the value of integrated respiratory specialists. Method: A questionnaire was sent to all BTS members in Oct 2013 on the role of integrated care specialists, 216 responses were received. Results: Most respondents (82.5%, 178/216) included integration of primary and secondary care in their definition of integrated care, only 36.5% (65/178) included community, and a smaller number included social care as part of the definition. In the free-text there was also emphasis on the bridging role of the post, and providing "seamless care" across sectors. 62% (86/139) agreed that integrated respiratory specialists had added value (compared to respiratory specialist roles); providing continuity of care for a defined population (87%, [121/139), and 77% (106/138) agreed that they improve outcomes for patients with a long term condition. Eighty-nine percent (124/140) also agreed that integrated specialists improve relationships between primary and secondary care. When asked the most important role that an integrated respiratory specialist should undertake (98 comments), the provision of specialist leadership, clinical decision-making and supervision (20 comments) were highly rated. Teaching (10 comments) and providing liaison support for the whole pathway were also important (9 comments). Conclusion: 82% of respondents (178/216) included integration of primary and secondary care in their definition of integrated care. However 14.4% were unsure of what integrated care was. Considerable more work is needed to promote this new way of working and potential career pathway. However of those who did know about these roles, a large majority agreed that these roles had added value compared to traditional specialist roles. Funded by the BTS. Abstracts M35 to M43 can be found on pages A208–A211: